Bioavailability of a Nanoemulsion of Lutein is Greater than a Lutein Supplement - Rohini Vishwanathan; Thomas A. Wilson; Robert J. Nicolosi (Nano Biomedicine and Engineering, 2009)
Lutein, a lipid soluble, oxygenated carotenoid, has shown beneficial effects against the risk factors associated with age-related macular degeneration, cardiovascular disease and also damaging UV radiation. The goal of the present study was to formulate lutein into a stable hydrophilic nanoemulsion that is more bioavailable and consumable in a matrix such as a beverage rather than just supplements. A Microfluidizer® Processor was used to convert an oil-in-water lutein emulsion into a nanoemulsion that is a stable water dispersion and measures 150 nm. After a one wk baseline phase, subjects consumed a lutein supplement pill followed by a lutein nanoemulsion added to orange juice (6 mg/d and 2 mg/d in two separate studies) for one wk each with a 2 wk washout phase between treatments. In study 1, mean serum lutein concentrations (n = 9) increased by 104% (P < 0.001) and 167% (P < 0.001) after the 6 mg supplement and nanoemulsion phases, respectively. In study 2, mean serum lutein concentrations (n = 11) increased by 37% (P < 0.05) and 75% (P < 0.001) after the 2 mg lutein supplement and nanoemulsion phases, respectively Despite the fact that the actual concentration of lutein in the 6 mg and 2 mg nanoemulsions was 10% and 40% lower compared to the supplement form, respectively, due to Microfluidizer ® processor preparation loss, the nanoemulsions resulted in 31% (P < 0.05) and 28% (P < 0.05) greater serum lutein concentrations compared to the supplement.. In conclusion, nanoemulsions of lutein had significantly greater bioavailability than the supplement-pill forms.